2010
DOI: 10.1007/s00417-010-1307-z
|View full text |Cite
|
Sign up to set email alerts
|

Verteporfin PDT for non-standard indications—a review of current literature

Abstract: The complex pathogenesis of CNV provides a rationale for investigating combination approaches comprising verteporfin PDT and anti-VEGF therapies. Randomized controlled studies are warranted to confirm the preliminary results of verteporfin PDT as a monotherapy or in combination with anti-VEGF therapies in the treatment of a variety of choroidal vascular conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 99 publications
(98 reference statements)
2
37
0
2
Order By: Relevance
“…Interestingly, these results suggested that the oxidative/antioxidative balance shifts towards the antioxidative status and PDT with Verteporfin caused growth cycle arrest that helps to prevent further damage and give the cell time to repair the defect. These results agree with previous reports of Nowak-Sliwinska et al (2006) and Chan et al (2010). They concluded that, damaged endothelium is known to release procoagulant and vasoactive factors through the lipo-oxygenase (leukotriene) and cyclo-oxygenase (eicosanoids such as thromboxane) pathways, resulting in platelet aggregation, fibrin clot formation and vasoconstriction.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Interestingly, these results suggested that the oxidative/antioxidative balance shifts towards the antioxidative status and PDT with Verteporfin caused growth cycle arrest that helps to prevent further damage and give the cell time to repair the defect. These results agree with previous reports of Nowak-Sliwinska et al (2006) and Chan et al (2010). They concluded that, damaged endothelium is known to release procoagulant and vasoactive factors through the lipo-oxygenase (leukotriene) and cyclo-oxygenase (eicosanoids such as thromboxane) pathways, resulting in platelet aggregation, fibrin clot formation and vasoconstriction.…”
Section: Discussionsupporting
confidence: 93%
“…Verteporfin was used in conjunction with a laser to eliminate the abnormal blood vessels in the eye associated with conditions such as the wet form of macular degeneration. Verteporfin accumulates in these abnormal blood vessels and, when stimulated by non-thermal red light laser in the presence of oxygen, produces highly reactive short-lived singlet oxygen and other reactive oxygen radicals, resulting in local damage to the endothelium and blockage of the vessels (Nowak-Sliwinska et al 2006;Chan et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A suspected higher frequency among Asians, Caucasians and Hispanics as compared to African Americans (Chan et al, 2010;Yannuzzi, 1987) was not confirmed in all studies (Desai et al, 2003). A more severe form of CSCR with lower visual acuity seems to affect the African American subjects.…”
Section: Epidemiologymentioning
confidence: 90%
“…Subfoveal choroidal neovascular degeneration (CNV) is another area of significant interest for PDT [152]. CNV can occur as a complication of inflammatory conditions [153] and a combination of verteporfin PDT and immunosuppression has shown promise for inflammatory subfoeval CNV [154][155][156][157][158]. Photodynamic therapy with verteporfin is currently the only photosensitizer that is approved by regulatory agencies for the treatment of CNV secondary to pathologic myopatia and has shown beneficial effects [159].…”
Section: Current Developmentsmentioning
confidence: 99%